PENGARUH PENGELUARAN PEMERINTAH SEKTOR KESEHATAN, PENDIDIKAN DAN INFRASTRUKTUR TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI PAPUA - Resubun, Rizal; Yudha, I Made Endra Kartika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 5 (2024): Vol.13.No.5. MEI 2024 [307-392]DO - 10.24843/EEP.2024.v13.i05.p01, 2024)
Poverty is a fundamental problem and has become the concern of every country, especially developing countries. Indonesia as a country that is still developing, the problem of poverty is still a key issue that requires more attention. Poverty t is one of the t problem faced t by the Indonesian government, both at the national and regional levels. The purpose of this study was to analyze the effect of government spending on health, education and infrastructure simultaneously and partially on poverty in the districts/cities of Papua Province. This study used secondary data using panel data analysis method consisting of cross section data and time series data in Papua Province with a total of 340 observations. Research with a fixed effect model shows that government expenditure in the health, education and infrastructure sectors simultaneously influences poverty in the districts/cities of Papua Province. Government expenditure on health, education, and infrastructure partially has a statistic significant effect and has has negative relationship to poverty in the Regency/City of Papua Province. keyword : health expenditure, Education expenditure, Infrastructure expenditure, Poverty.